Evaluation of 532 nm Q-Switched Nd:YAG Laser and Acid Etching of Class V Composite Restoration: Comparative Histological Study - Ridha, Hayder K.; Al-Azzawi, Lehadh M. (Iraqi Journal of Laser, 2019)
Laser etching may be an alternative to acid etching of enamel and dentin. Several characteristics of irradiated dental hard tissues have been considered advantageous, microscopically rough surfaces without demineralization, open dentinal tubules without smear layer production and dentin surface sterilization. The aim of this study is to determine and compare histology the microleakage in class V cavity restored with a light cured composite after conditioning the samples(tooth surface) with 1-acid etching, 2-Q-switched Nd:YAG Laser etching and finally 3- acid and laser etching. Materials and methods: Twenty four non carious human extracted teeth were used in this study. The samples were equally grouped into four groups of six teeth each. A class V cavity was prepared. In group I, tooth surface was etched with a 37% phosphoric acid gel. In group II, the tooth surface was conditioned using a pulsed Nd:YAG Laser alone with a wavelength of 532 nm. The parameters were of pulse energy 60 mJ, pulse repetition rate 6Hz and energy density was 0.48 J/cm2. In group III, the tooth surface was treated with Nd: YAG Laser and then was etched with phosphoric acid. In group IV, the surface was treated with 37% phosphoric acid then irradiated with Nd: YAG Laser; with the same parameters and concentration mentioned in group I and II. The samples immersed in 1% basic fuschin dye to mimic the normal stains in oral cavity and the sections were examined by a stereomicroscope and the readings were scored. Results: The results showed that group IV, in which the surface was treated with 37% phosphoric acid and then irradiated with Nd: YAG Laser) recorded the least microleakage of the four groups, where group III, in which the tooth surface was treated with Nd: YAG Laser and then was etched with phosphoric acid)recorded reasonable results better than group I (group I tooth surface was etched with a 37% phosphoric acid gel) or group II , in which the tooth surface was conditioned using a pulsed Nd:YAG Laser alone) Conclusion: The use of Q-switched Nd:YAG laser in etching the tooth surface was so effective that it can be used in treating or conditioning the tooth surface to enhance bonding and the best parameters among the tested samples were pulse energy of 60mJ, pulse repetition rate of 6Hz and energy density 0.48 J/cm2.